The regulatory roles of NADPH oxidase, intra- and extra-cellular HSP70 in pancreatic islet function, dysfunction and diabetes - Krause, Mauricio; Bock, Patricia Martins; Takahashi, Hilton Kenji; Homem De Bittencourt, Paulo Ivo; Newsholme, Philip (Clinical science (1979), 2015)
The 70 kDa heat-shock protein (HSP70) family is important for a dynamic range of cellular processes that include protection against cell stress, modulation of cell signalling, gene expression, protein synthesis, protein folding and inflammation. Within this family, the inducible 72 kDa and the cognate 73 kDa forms are found at the highest level. HSP70 has dual functions depending on location. For example, intracellular HSP70 (iHSP70) is anti-inflammatory whereas extracellular HSP70 (eHSP70) has a pro-inflammatory function, resulting in local and systemic inflammation. We have recently identified a divergence in the levels of eHSP70 and iHSP70 in subjects with diabetes compared with healthy subjects and also reported that eHSP70 was correlated with insulin resistance and pancreatic β-cell dysfunction/death. In the present review, we describe possible mechanisms by which HSP70 participates in cell function/dysfunction, including the activation of NADPH oxidase isoforms leading to oxidative stress, focusing on the possible role of HSPs and signalling in pancreatic islet α- and β-cell physiological function in health and Type 2 diabetes mellitus.